A Christmas story - Brown, Leigh; Clark, Bob; Dupont, Rene; Sheperd, Jean (MGM/UA Video, 1983)
All Ralphie Parker wants for christmas is a genuine Red Ryder carbine action two hundred shot lightning loader range model air rifle.